Ribosomal DNA phylogenies of Cyathus: Is the current infrageneric classification appropriate? - Zhao, Rui Lin; Jeewon, Rajesh; Desjardin, Dennis E.; Soytong, Kasem; Hyde, Kevin D. (My University, 2007)
Phylogenetic relationships within the genus Cyathus (bird's nest fungi) were investigated with neighbor joining, maximum likelihood, weighted maximum parsimony and MrBayes analyses of ITS and LSU ribosomal DNA sequences datasets. Twenty-two taxa of Cyathus were used in the analyses based primarily on type and authentic specimens. The current infrageneric classification system of Brodie recognizes seven infrageneric groups based on morphological characters, including peridium plications and variations in peridium hair anatomy, peridiole structure and fruit-body color. These groups are not supported by molecular data. Instead the ITS and LSU datasets support recognition of three infrageneric groups herein named the ollum, pallidum and striatum groups. Morphological characters useful in distinguishing these groups include basidiospore size, fruit-body coloration and peridium anatomy. Cyathus africanus var. latisporus is considered a synonym of Cyathus jiayuguanensis, and a new combination Cyathus lanatus (Brodie) R.L. Zhao is proposed based on morphological and molecular data. © 2007 by The Mycological Society of America.
Keywords: Bird's nest fungi; Gasteromycetes; Nidulariaceae; Phylogenetics; Taxonomy